2004
DOI: 10.1017/s1092852900009780
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Psychosocial Practices: Lessons Learned from Statewide Implementation of Two Practices

Abstract: Original Research FOCUS POINTS• Implementation of evidence-based practices is greatly affected by funding, credentialing, history of the practice within the local service system, and the availability of technical support, as well as by the structure of the practice itself.• Strong leadership and mastery of practicerelated skills were the two most prominent factors that impacted implementation efforts.• Program planners often underestimate the amount of time it will take to achieve full implementation of a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 29 publications
4
74
0
Order By: Relevance
“…The implementation of evidence-based practices is a complex process and is dependent on structural aspects of the local public mental system. As noted by Drake et al (2009) 3 in a review of the implementation of evidence-based practices in schizophrenia, factors that are important to successfully disseminating psychosocial evidence-based practices include the state mental health authority's provision of leadership, funding, and practice standards [224][225][226] skilled mentoring and training; 227 site level administrative support 224,[227][228][229][230][231] and monitoring of fidelity and outcomes. 232,233 Until clinical service settings can administer evidence-based practices as they are developed and studied, the problem of the imperfect and inadequate application of research to clinical practice will persist.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of evidence-based practices is a complex process and is dependent on structural aspects of the local public mental system. As noted by Drake et al (2009) 3 in a review of the implementation of evidence-based practices in schizophrenia, factors that are important to successfully disseminating psychosocial evidence-based practices include the state mental health authority's provision of leadership, funding, and practice standards [224][225][226] skilled mentoring and training; 227 site level administrative support 224,[227][228][229][230][231] and monitoring of fidelity and outcomes. 232,233 Until clinical service settings can administer evidence-based practices as they are developed and studied, the problem of the imperfect and inadequate application of research to clinical practice will persist.…”
Section: Discussionmentioning
confidence: 99%
“…McFarlane et al (2001) concluded that a strong positive relationship between the SMHA and the provider community was a key ingredient in the success of statewide implementation of family psychoeducation. In a case study of one state, Moser et al (2004) identified state-level factors associated with successful implementation of one EBP compared with poor implementation of another EBP. A comparison between implementation of assertive community treatment in two states highlighted the far-reaching impact of state policy (Mancini et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One study (Moser et al 2004) compared the implementation of two EBPs in the same service system: assertive community treatment (ACT) and integrated dual disorders treatment (IDDT). The authors noted that differences in model structures (e.g., staff positions, caseload ratios) and skill sets (e.g., motivational interviewing) required varying levels and types of training and consultation.…”
Section: Introductionmentioning
confidence: 99%